New Trends Towards Enhanced Structural Efficiency and Aesthetic Potential in Tall Buildings: The Case of Diagrids - Domenico Scaramozzino (Applied Sciences, 2020)
Due to the increasing number of people and activities within the cities, tall buildings are exploited worldwide to address the need for new living and commercial spaces, while limiting the amount of used land. In recent decades, the design of tall buildings has undergone a remarkable improvement, thanks to the development of new computational tools and technological solutions. This has led to the realization of innovative structural systems, like diagrids, which allow the achievement of high structural performances and remarkable architectural effects. In this paper, a thorough and updated review of diagrid structural systems is provided. Simplified methodologies for the preliminary design and structural analysis are reported. Special attention is also paid to the optimization of the structural response based on the geometrical pattern. A discussion of the effect of local deformability, stability and shear-lag phenomenon is carried out. Results from nonlinear and dynamic analyses for the seismic assessment of diagrid systems are reported, and attention is also paid to the recent research on diagrid nodes. Eventually, an overview of twisted, tapered, tilted and freeform diagrid towers is carried out, with a final mention of hexagrids, another recent evolution of tubular systems for tall buildings.